Ultra-high structure, high specific surface carbon black based on high crystallinity and preparation method thereof, electrode slurry, and battery

By preparing carbon black materials with high crystallinity and ultra-high structure, the problems of low crystallinity and unstable structure in existing carbon black in battery applications are solved, and the effect of improving conductivity and liquid absorption and liquid retention ability is achieved.

CN118398815BActive Publication Date: 2025-04-18JIAOZUO CITY HEXING CHEMICAL INDUSTRY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410483522.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2025-04-18
Estimated Expiration
2044-04-22

AI Technical Summary

Technical Problem

Existing carbon black materials have problems such as low crystallinity, unstable structure and poor durability in battery applications, especially in corrosion at high potential and high temperature.

Method used

An ultra-high structure, high specific surface carbon black based on high crystallinity is adopted, which includes a crystallinity of ≥39%, a BET specific surface area of ​​200-763 m2/g, an OAN of 334-548 mL/100g and an average particle size of the primary particles ≤35nm. The carbon black is prepared by pretreatment and activation etching treatment, avoiding secondary graphitization high-temperature treatment.

Benefits of technology

Without secondary graphitization high temperature treatment, the carbon black has high crystallinity, ultra-high structure and high specific surface area, which improves the conductivity of the material and the liquid absorption and liquid retention ability, and improves the conductivity of the electrode active material and the stability of the catalyst support.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118398815B_ABST
    Figure CN118398815B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of carbon black materials, and in particular to a high-crystallinity ultra-high structure, high specific surface carbon black, and a preparation method thereof, as well as an electrode slurry and a battery. The ultra-high structure, high specific surface carbon black with high crystallinity satisfies the following characteristics: (1) crystallinity ≥ 39%; (2) BET specific surface area of ​​200 to 763 m 2 / g; (3) OAN is 334-548mL / 100g; (4) the average particle size of the primary particles is ≤35nm. The carbon black of the present invention has high crystallinity, ultra-high structure and high specific surface area. When used as a conductive agent or carrier, the high graphitization degree of the carbon black can improve the conductivity of the electrode active material and the compatibility with the electrolyte or improve the stability of the carrier material to ensure the activity of the catalyst; at the same time, the carbon black of the present invention has excellent liquid absorption and retention capacity and catalyst loading stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon black materials, and in particular to an ultra-high structure and high specific surface carbon black based on high crystallinity, a preparation method thereof, an electrode slurry and a battery. Background Art

[0002] In recent years, carbon black has been commonly used in battery fields such as lithium-ion secondary batteries and fuel cells. The general structure of lithium-ion secondary batteries is mainly composed of positive electrode, negative electrode, separator and electrolyte. Carbon black is used as a conductive agent to improve the conductivity of the positive electrode active material, which requires carbon black to have high structure, high crystallinity and high dispersibility to build a rich conductive network and good intrinsic conductivity. Carbon black is used as a catalyst carrier in fuel cells. The carrier particles should have a high surface area to maximize the contact between reactants and catalysts and improve the catalytic efficiency. However, due to corrosion under high potential and high temperature of the battery, the specific surface area of ​​carbon black accounts for a large proportion of the specific surface area of ​​the formula powder material, although the amount added is small. The durability and stability of the commonly used carbon black carrier are the main problems.

[0003] For the above reasons, carbon black preferably has a higher structure, specific surface area and degree of graphitization. Furnace carbon black is favored because of its high specific surface area, but the product has low crystallinity and poor long-term stability. In addition, since the impurities in the raw materials are not easy to remove, the impurities in the carbon black product are more, which further hinders its long-term stability and affects its application. In addition, in order to increase the specific surface area of ​​carbon black, carbon black is usually etched with oxidants such as air, oxygen, ozone, and water vapor at a temperature of 500-950°C. However, the carbon black after oxidation treatment has low crystallinity and requires further high-temperature graphitization treatment. On the one hand, the graphitization temperature is about 2000-3000°C, and the energy consumption is large; on the other hand, during the high-temperature heat treatment process, as the degree of graphitization of carbon black increases, the carbon black structure collapses, and the total (internal) surface area tends to decrease, thereby reducing the electrolyte adsorption and storage properties of carbon black. In addition, the chain branch structure of carbon black after oxidation etching is broken or dissociated, resulting in the carbon black structure after etching not being greatly improved.

[0004] The existing product Ketjen Black has a high specific surface area and rich branched morphology. It can achieve high conductivity with a small amount of addition. It is suitable for high-end fields such as high-performance batteries and has long been in a leading position in the market. However, Ketjen Black is prepared by the oil furnace method, which has a low generation temperature and a large amount of oxygen contact, resulting in low crystallinity of Ketjen Black. The average particle size of Ketjen Black's primary particles is 40nm, which is equivalent to the particle size of commercially available SP and acetylene carbon black, that is, the number of primary particles of the same mass of carbon black is equivalent. In addition, the production of Ketjen Black products is difficult, the product yield is low, and the production cost is high.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide ultra-high structure, high specific surface area carbon black based on high crystallinity and its preparation method, electrode slurry and battery. The carbon black of the present invention has high crystallinity, ultra-high structure and high specific surface area without the need for secondary graphitization high temperature treatment, which can improve the conductivity of the material and enhance the liquid absorption and retention capacity.

[0007] In order to achieve the above-mentioned object of the present invention, the present invention provides, on one hand, an ultra-high structure and high specific surface carbon black based on high crystallinity, wherein the carbon black satisfies the following characteristics:

[0008] (1) Crystallinity ≥ 39%;

[0009] (2) BET specific surface area is 200 to 763 m 2 / g;

[0010] (3) OAN is 334-548 mL / 100 g;

[0011] (4) The average particle size of primary particles is ≤35nm.

[0012] In a specific embodiment of the present invention, the crystallite size Lc of the carbon black is

[0013] In a specific embodiment of the present invention, the crystallite size La of the carbon black is

[0014] In a specific embodiment of the present invention, the lattice fringes of the primary particles of the carbon black are in the shape of irregular bamboo hat bands or rings.

[0015] In a specific embodiment of the present invention, the crystallinity of the carbon black is 39% to 46%.

[0016] In a specific embodiment of the present invention, the aggregate size D50 of the carbon black is ≤95nm. Further, the aggregate size D50 of the carbon black is ≥68nm.

[0017] In a specific embodiment of the present invention, the average lattice spacing d(002) of the carbon black is ≤0.3534 nm, such as 0.3479-0.3534 nm.

[0018] In a specific embodiment of the present invention, the average particle size of the primary particles of the carbon black is 25 to 35 nm.

[0019] In a specific embodiment of the present invention, the average pore size of the carbon black is 5.86-9.04 nm.

[0020] In a specific embodiment of the present invention, the volume of pores with a size of 2 to 50 nm measured by nitrogen desorption of the carbon black is 0.3157 to 1.2061 cm 3 / g.

[0021] In a specific embodiment of the present invention, in the carbon black, the volume of pores with a size of 2 to 50 nm accounts for 84.6% to 93.8% of the total pore volume.

[0022] Another aspect of the present invention provides a method for preparing any one of the above-mentioned carbon blacks, comprising the following steps:

[0023] The pretreated raw carbon black is subjected to activation etching treatment;

[0024] The activation etching process comprises: heating to a first activation temperature under a protective atmosphere, performing an activation process under the action of an activation gas; cooling to a second activation temperature, performing an etching process under the action of an activation gas; and then cooling to room temperature under a protective atmosphere;

[0025] The pretreatment comprises: treating the raw carbon black in an aqueous solution containing an oxidant at 30 to 150° C. for 0.5 to 2 hours, washing and drying;

[0026] The first activation temperature is 1100-1500° C.; the second activation temperature is 900-1000° C.; and the crystallinity of the raw carbon black is ≥44%.

[0027] In a specific embodiment of the present invention, the specific surface area of ​​the raw carbon black is 60 to 150 m 2 / g. Further, the raw material carbon black is acetylene black.

[0028] In a specific embodiment of the present invention, the activated gas includes at least one of nitrogen dioxide, nitric oxide, CO2, CO, oxygen, ozone and water vapor.

[0029] In a specific embodiment of the present invention, the activation treatment time at the first activation temperature is 10 to 30 minutes.

[0030] In a specific embodiment of the present invention, the etching treatment time at the second activation temperature is 30 to 70 minutes.

[0031] In a specific embodiment of the present invention, during the cooling, the cooling rate is 2 to 4°C / min.

[0032] In a specific embodiment of the present invention, during the heating, the heating rate is 4-6°C / min.

[0033] In a specific embodiment of the present invention, the oxidant includes at least one of hydrogen peroxide and an oxygen-containing acid. Further, the oxygen-containing acid includes at least one of nitric acid, sulfuric acid, hypochlorous acid and perchloric acid.

[0034] Another aspect of the present invention provides an electrode slurry, comprising any one of the carbon blacks described above.

[0035] Another aspect of the present invention provides a secondary battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator; at least one of the positive electrode and the negative electrode is made from any one of the electrode slurries described above.

[0036] Another aspect of the present invention provides a fuel cell, comprising a catalyst, wherein the catalyst comprises a carrier and active catalyst particles supported on the carrier; the carrier comprises any one of the above-mentioned carbon blacks.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The carbon black of the present invention has high crystallinity, ultra-high structure and high specific surface area. When used as a conductive agent or carrier, the high graphitization degree of the carbon black can improve the conductivity of the electrode active material and the compatibility with the electrolyte or improve the stability of the carrier material to ensure the activity of the catalyst; at the same time, the carbon black of the present invention has excellent liquid absorption and retention capacity and catalyst loading stability;

[0039] (2) The method for preparing carbon black of the present invention uses carbon black with a certain degree of crystallinity as a raw material, uses an oxidant for pretreatment to initially oxidize the carbon black, and then performs subsequent activation and etching to form ultra-high structure, high specific surface area carbon black, and avoid collapse, so that the prepared carbon black has both liquid absorption and retention capabilities and excellent conductive properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 This is a scanning electron microscope image of the carbon black prepared in Example 3 of the present invention;

[0042] Figure 2 TEM images of carbon black prepared in Example 3 of the present invention, wherein (a) to (c) are transmission electron microscope images at different magnifications, respectively;

[0043] Figure 3The Raman spectrum of the carbon black prepared in Example 1 of the present invention;

[0044] Figure 4 The Raman spectrum of the carbon black prepared in Example 2 of the present invention;

[0045] Figure 5 The Raman spectrum of the carbon black prepared in Example 3 of the present invention;

[0046] Figure 6 The Raman spectrum of the raw carbon black used in the embodiment of the present invention;

[0047] Figure 7 is the Raman spectrum of the carbon black of Comparative Example 1;

[0048] Figure 8 is the Raman spectrum of the carbon black of Comparative Example 2;

[0049] Fig. 9 is the aggregate size distribution curve of the carbon black prepared in Example 1 of the present invention;

[0050] Fig.10 is the aggregate size distribution curve of the carbon black prepared in Example 2 of the present invention;

[0051] Fig.11 is the aggregate size distribution curve of the carbon black prepared in Example 3 of the present invention;

[0052] Fig.12 is the aggregate size distribution curve of the raw material carbon black used in the embodiment of the present invention;

[0053] Fig.13 is the aggregate size distribution curve of the carbon black of Comparative Example 1;

[0054] Fig.14 is the aggregate size distribution curve of the carbon black of Comparative Example 2;

[0055] Fig.15 The XRD spectra of the carbon black of Examples 1 to 3 and Comparative Examples 1 to 2 of the present invention and the raw material carbon black are shown. DETAILED DESCRIPTION

[0056] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0057] When carbon black is used as a conductive agent in secondary batteries, it is required to be able to build a rich conductive network, have good intrinsic conductivity, and have a certain ability to absorb and retain liquid; when carbon black is used as a catalyst carrier in fuel cells, it is required to have a high specific surface area and stability. The above-mentioned multi-performance requirements require that multiple parameters of carbon black meet a certain range of requirements at the same time. However, the carbon black in the prior art cannot meet the above-mentioned multiple performances at the same time.

[0058] Based on this, the present invention provides, on one hand, an ultra-high structure and high specific surface carbon black based on high crystallinity, and the carbon black satisfies the following characteristics:

[0059] (1) Crystallinity ≥ 39%;

[0060] (2) BET specific surface area is 200 to 763 m 2 / g;

[0061] (3) OAN is 334-548 mL / 100 g;

[0062] (4) The average particle size of primary particles is ≤35nm.

[0063] The carbon black of the present invention has high crystallinity, ultra-high structure and high specific surface area. When used as a conductive agent or carrier, the high graphitization degree of the carbon black can improve the conductivity of the electrode active material and the compatibility with the electrolyte or improve the stability of the carrier material to ensure the activity of the catalyst; at the same time, the carbon black of the present invention has excellent liquid absorption and retention capabilities and catalyst loading stability.

[0064] The degree of graphitization of carbon black can be characterized by its crystallinity, which is measured in Raman spectroscopy as the ratio of the area of ​​the G band to the sum of the areas of the G band and the D band (S G / S G+D). The crystallinity of the carbon black of the present invention is ≥39%, such as 39% to 46%, which is significantly improved compared to the crystallinity of the existing carbon black, indicating that the carbon black of the present invention can obtain a high degree of graphitization. When the carbon black of the present invention is used as a conductive agent or carrier, the high graphitization degree of the carbon black can improve the conductivity of the electrode active material and the compatibility with the electrolyte or improve the stability of the carrier material to ensure the activity of the catalyst. In the carbon black of the present invention, the crystallinity can be 39%, 40%, 42%, 43%, 44%, 45%, 46% or a range composed of any two of them.

[0065] The Raman spectrum test method and parameters of the present invention can be referred to as follows:

[0066] Using a laser Raman spectrometer, several test objects were placed on a glass slide and scraped several times with a spatula to make it flat. The test was performed under the following test conditions: YAG laser (excitation wavelength): 514nm, number of lines: 600gr / mm, filter: D0.6, objective lens magnification: 100x, exposure time: 150 seconds, accumulation times: 2 times.

[0067] The BET specific surface area is tested according to the method of GB / T 19587-2004. Generally, the BET specific surface area of ​​carbon black can reflect the development of the void structure of carbon black. The BET specific surface area of ​​the present invention is 200 to 763 m 2 / g, indicating that it has a developed void structure and chain branch structure, which increases the number of contact points with other substances and can give full play to the conductivity of carbon black; at the same time, it is conducive to accommodating and loading catalysts. In the carbon black of the present invention, the BET specific surface area of ​​carbon black can be 200m 2 / g, 213m 2 / g, 250m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g, 572m 2 / g、600m 2 / g, 650m 2 / g, 691m 2 / g、700m 2 / g、728m 2 / g, 763m 2 / g or a range consisting of any two of them.

[0068] Carbon black raw materials are first cracked into small molecular gases or ions in a high temperature, oxygen-deficient or anaerobic environment, and then these ions or molecules are deposited into nuclei and form primary particles of carbon black. At high temperatures, primary particles are complexly arranged into chemically bonded branches or chain aggregates, forming the primary structure of carbon black; the primary structure is a structure formed by strong chemical bonds between aggregates, which is a permanent structure; the aggregates are aggregated again into larger aggregates through electrostatic forces, forming the secondary structure of carbon black. The secondary structure is a weak or unstable structure formed by van der Waals forces between carbon black aggregates, which is not a permanent structure; the void volume generated by these aggregated carbon black aggregates is a measure of the carbon black structure and can be characterized by the oil absorption number (OAN), which is determined by the standard method of "GB / T3780.2-2017 Carbon Black Part 2: Determination of Oil Absorption Number". In the carbon black of the present invention, the OAN of the carbon black can be 334mL / 100g, 360mL / 100g, 380mL / 100g, 400mL / 100g, 405mL / 100g, 420mL / 100g, 446mL / 100g, 450mL / 100g, 460mL / 100g, 480mL / 100g, 500mL / 100g, 548mL / 100g or a range composed of any two thereof.

[0069] The average particle size of the primary particles of the carbon black of the present invention is relatively small ≤ 35nm, such as 25 to 35nm. The increase in the number of primary particles of the same mass of carbon black can further increase the contact points, which is conducive to forming more conductive paths. In the carbon black of the present invention, the average particle size of the primary particles can be 25nm, 28nm, 30nm, 32nm, 35nm or a range consisting of any two of them. The average particle size of the primary particles is the value obtained by averaging the particle sizes measured by photos taken with a transmission electron microscope, and the particle size is the circle equivalent diameter calculated from the area of ​​the primary particles.

[0070] In a specific embodiment of the present invention, the crystallite size Lc of carbon black is

[0071] The crystallite size Lc is a factor indicating the crystallinity of the carbon material having a crystal structure, and can be calculated by the following Scherrer equation based on X-ray diffraction data analyzed by X-ray diffraction (XRD).

[0072] Scherrer equation: Lc=0.89λ / (βCosθ)

[0073] where 0.89 is the Scherrer constant, λ is the wavelength, θ is the angle at the d-spacing (002) peak, and β is the full width maximum at the d-spacing (002) peak.

[0074] Compared with the crystallite size Lc of the raw carbon black, the crystallite size Lc of the carbon black of the present invention is significantly increased, which greatly improves the crystallinity of the carbon black, and also shows that the graphitization degree of the carbon black of the present invention is significantly improved. In the carbon black of the present invention, the crystallite size Lc can be Or a range consisting of any two of them.

[0075] In a specific embodiment of the present invention, the crystallite size La of carbon black is

[0076] The Raman spectrum of carbon includes a wavelength of about 1340 cm -1 and 1580cm -1 There are two main "resonance" bands at , denoted as "D" and "G" bands. It is generally believed that the D band is attributed to the disordered sp 2 Carbon, G band is attributed to graphitic or "ordered" sp 2 Carbon, regression analysis yields the following empirical relationship: La = 43.5 × (area of ​​G band / area of ​​D band), where La is calculated in angstroms. The crystal domains of the ultra-high structure, high specific surface area carbon black based on high crystallinity of the present invention can be characterized by the crystallite size (La), and the La crystallite size is measured by Raman spectroscopy. La is defined as 43.5 × (area of ​​G band / area of ​​D band). The crystallite size can give an indication of the degree of graphitization, wherein a higher La value is associated with a higher degree of graphitization. The crystallite size La of the carbon black of the present invention is It can be shown that the carbon black of the present invention has a high degree of graphitization. In the carbon black of the present invention, the crystallite size La can be Or a range consisting of any two of them.

[0077] In a specific embodiment of the present invention, the lattice fringes of the primary particles of carbon black are in the shape of irregular bamboo hat bands or rings.

[0078] In a specific embodiment of the present invention, the aggregate size D50 of the carbon black is ≤95 nm. Further, the aggregate size D50 of the carbon black is ≥68 nm.

[0079] The carbon black aggregate size distribution curve of the present invention is measured by a disc centrifugal sedimentation particle size analyzer (Brookhaven Instruments Corporation, BI-DCP), and the test method refers to GB / T3780.27-2020. The specific test method can be referred to as follows:

[0080] (1) Preparation of carbon black dispersion: Weigh 20 mg of carbon black sample, add 20 mL of dispersion (rotating liquid: ethanol = 4:1 (volume ratio)), adjust the pH value to 9-10, ultrasonically treat at 50 W for 5 min, then ultrasonicate for 10 min using a cell crusher, and ultrasonicate at 50 W for 5 min again. The carbon black dispersion is allowed to cool to room temperature for later use; wherein, 0.5 g of Triton X-100 and 5 drops of ammonia water are added to softened water to prepare 1000 mL of rotating liquid;

[0081] (2) Turn on the power of the particle size analyzer and wait for 30 minutes to allow the equipment to enter a stable state;

[0082] (3) Turn on the particle size analyzer computer and set the following parameters: measurement time 60 min; rotation speed 7000 rpm; particle density 1.860 g / cm 3 ; Temperature 25℃;

[0083] (4) Use a syringe to inject 1 mL of ethanol and press the motor at the same time; immediately inject 15 mL of rotating liquid and 0.1 mL of dodecane in sequence, wait for 3 to 5 minutes, and then add 0.25 mL of carbon black dispersion after the signal value stabilizes, and start the instrument measurement program; stop the test when the signal value approaches the baseline after about 30 to 60 minutes; click zoom to adjust the baseline so that the baseline area is parallel; repeat the measurement twice for each measurement sample.

[0084] D50 is the particle size corresponding to when the cumulative particle size distribution percentage of carbon black aggregate particles reaches 50%. The aggregate size distribution of the carbon black prepared by the present invention is similar to the aggregate size distribution curve of the raw carbon black, and according to the D50 value, it can be seen that the carbon black after oxidation etching of the present invention maintains the structural size of the aggregate of the raw carbon black, and does not destroy the rich chain branch structure of the carbon black, thereby making it have excellent liquid absorption and retention capabilities. The aggregate size D50 of the carbon black of the present invention is 68 to 95nm, such as 68nm, 72nm, 75nm, 78nm, 80nm, 82nm, 84nm, 88nm, 90nm, 95nm or a range consisting of any two of them.

[0085] In a specific embodiment of the present invention, the average lattice spacing d(002) of carbon black is ≤0.3534 nm, such as 0.3479-0.3534 nm.

[0086] The degree of graphitization of carbon materials can also be characterized by their "d spacing". The average lattice spacing d(002) of the present invention is defined as the average distance between adjacent hexagonal rings in the c-axis direction, which is determined by the XRD (002) diffraction peak. The d(002) spacing can be calculated according to Bragg's law using the following formula:

[0087] d=λ / (2Sinθ)

[0088] Where: λ = wavelength of the radiation source (for copper, λ is ), θ = diffraction angle (unit: degree) (peak 002), d = spacing between two carbon layer planes.

[0089] The average lattice spacing d(002) of the conductive carbon black of the present invention is ≤0.3534nm, such as 0.3479-0.3534nm, which is greatly reduced relative to the d(002) spacing of the raw carbon black, indicating that the etching of the present invention reduces the lattice spacing and improves the crystallinity of the carbon black. In addition, the d(002) of the carbon black of the present invention is close to or less than 0.3500nm, further indicating that the carbon black of the present invention is graphite carbon, which improves the stability of the carbon black. For example, in different embodiments, the average lattice spacing d(002) of the carbon black of the present invention can be 0.3479nm, 0.349nm, 0.35nm, 0.351nm, 0.3515nm, 0.352nm, 0.3525nm, 0.353nm, 0.3534nm or a range consisting of any two of them.

[0090] In a specific embodiment of the present invention, the average pore size of carbon black is 5.86-9.04 nm. For example, in different embodiments, the average pore size of carbon black can be 5.86 nm, 6 nm, 6.2 nm, 6.4 nm, 6.59 nm, 6.8 nm, 7 nm, 7.2 nm, 7.41 nm, 8.5 nm, 9.04 nm, or a range consisting of any two thereof.

[0091] In a specific embodiment of the present invention, the volume of pores with a size of 2 to 50 nm measured by nitrogen desorption of carbon black is 0.3157 to 1.2061 cm 3 In different embodiments, the volume of pores with a size of 2 to 50 nm can be 0.3157 cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g, 0.6540cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.85cm 3 / g, 0.8689cm 3 / g, 1.2061cm 3 / g or a range consisting of any two of them.

[0092] In a specific embodiment of the present invention, in the carbon black, the volume of pores with a size of 2 to 50 nm accounts for more than 84.6% of the total pore volume, such as 84.6% to 93.8%. For example, in different embodiments, the volume of pores with a size of 2 to 50 nm accounts for 84.6%, 85%, 86.9%, 87%, 88%, 88.9%, 93.8% or a range consisting of any two thereof.

[0093] The present invention tests the pore parameters according to the method of GB / T 19587-2004. The pore volume of the carbon black of the present invention can be as high as 0.9773 cm 3 / g, and the proportion of mesopore (2-50nm) pore volume is more than 84.6%. Compared with the raw carbon black, the proportion of mesopore volume is significantly increased, which improves the liquid retention capacity of carbon black and is beneficial to the loading of catalyst. The developed mesoporous structure and large BET specific surface area show that the carbon black of the present invention has a developed void structure.

[0094] Another aspect of the present invention provides a method for preparing any one of the above carbon blacks, comprising the following steps:

[0095] The pretreated raw carbon black is subjected to activation etching treatment;

[0096] The activation etching process includes: heating to a first activation temperature under a protective atmosphere, and performing an activation process under the action of an activation gas; cooling to a second activation temperature, and performing an etching process under the action of an activation gas; and then cooling to room temperature under a protective atmosphere;

[0097] The pretreatment includes: treating the raw carbon black in an aqueous solution containing an oxidant at 30 to 150° C. for 0.5 to 2 hours, washing and drying;

[0098] The first activation temperature is 1100-1500°C; the second activation temperature is 900-1000°C; and the crystallinity of the raw carbon black is ≥44%.

[0099] The present invention uses raw carbon black with a certain degree of graphitization, and the surface of the primary particles of the raw carbon black has a high degree of graphitization. The crystallinity of the raw carbon black of the present invention is ≥44%, such as 44%, 45%, 46%, 48%, 50%, 51% or a range composed of any two thereof. The raw carbon black of the present invention contains a "shell" of larger and more perfect crystallites, and the crystallites have a layered plane that is generally oriented parallel to the particle surface, which minimizes the defects on the surface of the primary particles of the raw carbon black; the central area or "core" of the "shell" mainly contains small and imperfect crystallites, single-layer planes, and possibly irregular carbon that is not bound to the layered plane, i.e., "defects". In the preparation method of the present invention, the raw carbon black is first pretreated with an oxidant to make the carbon black initially oxidized, and then at a relatively high temperature (1100-1500° C.), the activated gas molecules (such as water molecules) and the oxygen-containing functional groups generated by the initial oxidation first attack the "defects" on the carbon surface, and remove carbon atoms from the surface and form gaseous CO or CO2 and hydrogen, resulting in the exposure of more carbon atoms or amorphous carbon, and the formation of more "defects", that is, activation. Then, at a suitable temperature (900-1000° C.), the carbon in the "core" is further etched to form a carbon black with a high specific surface and high structure. At the same time, since the "shell" has a high degree of graphitization, it will not dissociate or collapse due to the etching of some defects during the oxidation etching process, thereby ensuring a grape-like porous chain branch structure, maintaining the raw carbon black aggregate structure, and thus having a good liquid absorption and retention capacity and excellent electrical conductivity.

[0100] Appropriate pretreatment temperature and time can form appropriate defects on the carbon surface and generate appropriate oxygen-containing functional groups during the initial oxidation process. For example, in different embodiments, in the pretreatment, the raw carbon black is treated in an aqueous solution containing an oxidant at a temperature of 30°C, 50°C, 80°C, 100°C, 120°C, 150°C, or a range consisting of any two thereof; the treatment time can be 0.5h, 0.8h, 1h, 1.5h, 2h, or a range consisting of any two thereof.

[0101] At the higher first activation temperature of the present invention, the activated gas molecules and the oxygen-containing functional groups generated by the initial oxidation can attack the defects on the carbon surface and form a new gas phase, thereby forming more defects. In the preparation method of the present invention, the first activation temperature can be 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, or a range consisting of any two thereof.

[0102] The second activation temperature of the present invention is relatively low. Under this temperature condition, the "core" of the carbon black can be etched in a focused manner to form a carbon black with a high specific surface area and a high structure, while avoiding excessive etching and maintaining the original structure to avoid excessive damage. In the preparation method of the present invention, the second activation temperature can be 900°C, 920°C, 940°C, 950°C, 960°C, 980°C, 1000°C, or a range consisting of any two of them.

[0103] The protective atmosphere of the present invention may include at least one of nitrogen and argon. By cooling under the protective atmosphere, oxygen is prevented from oxidizing the surface of the product to reduce the crystallinity, and functional groups on the surface of the product can be removed.

[0104] In a specific embodiment of the present invention, the BET specific surface area of ​​the raw carbon black is 60 to 150 m 2 / g.

[0105] In the preparation method of the present invention, there is no restriction on the BET specific surface area of ​​the raw carbon black. For example, the BET specific surface area is 60 m 2 / g, 70m 2 / g, 80m 2 / g, 90m 2 / g、100m 2 / g, 110m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g etc., but not limited to these.

[0106] In a specific embodiment of the present invention, the raw material carbon black is acetylene black.

[0107] In a specific embodiment of the present invention, the activated gas includes at least one of nitrogen dioxide, nitric oxide, CO2, CO, oxygen, ozone and water vapor.

[0108] The use of the above-mentioned activation gas helps to attack the defects on the carbon surface during the activation process, thereby exposing more carbon atoms or amorphous carbon. In actual operation, the activation gas used in the activation treatment at the first activation temperature and the heat preservation treatment at the second activation temperature can be the same or different.

[0109] In a specific embodiment of the present invention, the activation treatment time at the first activation temperature is 10 to 30 minutes.

[0110] By adjusting the activation treatment time, the defects formed on the carbon surface of the raw carbon black at the first activation temperature can be adjusted. The appropriate activation treatment time helps to ensure the stability of the structure while the defects are formed. The activation treatment time of the present invention can be 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes or a range composed of any two of them.

[0111] In a specific embodiment of the present invention, the etching treatment time at the second activation temperature is 30 to 70 minutes.

[0112] Carrying out heat preservation etching for a certain period of time at the second activation temperature can ensure that the "core" of the carbon black is etched in a focused manner to increase the mesoporous structure; at the same time, it can avoid the etching time being too long, which may cause the collapse or dissociation of the primary particles of the carbon black. The etching time at the second activation temperature of the present invention can be 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, or a range consisting of any two of them.

[0113] In a specific embodiment of the present invention, during cooling, the cooling rate is 2 to 4°C / min, such as 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, etc.

[0114] In a specific embodiment of the present invention, during the heating process, the heating rate is 4 to 6°C / min, such as 4°C / min, 4.5°C / min, 5°C / min, 5.5°C / min, 6°C / min, etc.

[0115] In a specific embodiment of the present invention, the oxidant includes at least one of hydrogen peroxide and an oxygen-containing acid. Further, the oxygen-containing acid includes at least one of nitric acid, sulfuric acid, hypochlorous acid and perchloric acid.

[0116] In actual operation, the mass fraction of the oxidant in the aqueous solution containing the oxidant can be 20% to 70%, such as 20%, 35%, 50%, 60%, 70%, etc., but not limited thereto. The amount of the aqueous solution containing the oxidant is not limited, as long as the raw carbon black is immersed therein.

[0117] Another aspect of the present invention provides an electrode slurry comprising any one of the above-mentioned carbon blacks.

[0118] Another aspect of the present invention provides a secondary battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator; at least one of the positive electrode and the negative electrode is made of any one of the above-mentioned electrode slurries.

[0119] Among them, the types of positive electrode active materials, negative electrode active materials, electrolytes and isolation membranes can be adjusted according to actual needs and are not limited to a certain type. The following embodiments only use one active material, electrolyte and isolation membrane for illustration, rather than limiting these types.

[0120] Another aspect of the present invention provides a fuel cell, comprising a catalyst, wherein the catalyst comprises a carrier and active catalyst particles supported on the carrier; the carrier comprises carbon black.

[0121] The carbon black of the present invention is used as a catalyst carrier in a fuel cell, has an ultra-high structure and a high specific surface area, can maximize the contact between reactants and catalysts, and improve the catalytic efficiency; at the same time, the carbon black of the present invention has good structural stability, can improve the durability of the catalyst carrier, and extend the life of the battery. Among them, the type of active catalyst particles in the fuel cell can be adjusted according to actual needs and is not limited to a certain type.

[0122] The raw material carbon black used in the following examples is acetylene carbon black, and its BET specific surface area is 143m 2 / g, and the crystallinity is 44%, but not limited thereto.

[0123] Example 1

[0124] This embodiment provides a method for preparing ultra-high structure and high specific surface carbon black based on high crystallinity, comprising the following steps:

[0125] (1) The raw carbon black is added into a 20 wt% hydrogen peroxide aqueous solution, treated at 30° C. for 0.5 h, and then washed with water and dried to obtain a pretreated raw carbon black.

[0126] (2) The raw carbon black sample pretreated in step (1) is placed in a rotary furnace, nitrogen is introduced for protection, and then the furnace temperature is raised to 1100°C at a heating rate of 5°C / min, and then the nitrogen is cut off and nitrogen dioxide is introduced, and the temperature is kept at this temperature for 10 minutes. The nitrogen dioxide gas is turned off and water vapor is introduced, and the furnace temperature is lowered to 900°C at a cooling rate of 3°C / min, and the temperature is kept at this temperature for 30 minutes.

[0127] (3) Turn off the water vapor and introduce nitrogen, and naturally cool to room temperature under the protection of nitrogen to obtain ultra-high structure and high specific surface carbon black based on high crystallinity.

[0128] Example 2

[0129] This embodiment provides a method for preparing ultra-high structure and high specific surface carbon black based on high crystallinity, comprising the following steps:

[0130] (1) The raw carbon black is added into a 35 wt% nitric acid aqueous solution, treated at 60° C. for 1 h, and then washed with water and dried to obtain a pretreated raw carbon black.

[0131] (2) The raw carbon black sample pretreated in step (1) was placed in a rotary furnace, nitrogen was introduced for protection, and then the furnace temperature was raised to 1100° C. at a heating rate of 5° C. / min, and then the nitrogen was cut off and water vapor was introduced, and then the temperature was kept at this temperature for 20 minutes. Then the furnace temperature was lowered to 950° C. at a cooling rate of 3° C. / min, and then the temperature was kept at this temperature for 50 minutes.

[0132] (3) Turn off the water vapor and introduce nitrogen, and naturally cool to room temperature under the protection of nitrogen to obtain ultra-high structure and high specific surface carbon black based on high crystallinity.

[0133] Example 3

[0134] This embodiment provides a method for preparing ultra-high structure and high specific surface carbon black based on high crystallinity, comprising the following steps:

[0135] (1) The raw carbon black is added into a 70 wt% nitric acid aqueous solution, treated at 150° C. for 2 h, and then washed with water and dried to obtain a pretreated raw carbon black.

[0136] (2) The raw carbon black sample pretreated in step (1) was placed in a rotary furnace, nitrogen was introduced for protection, and then the furnace temperature was raised to 1400°C at a heating rate of 5°C / min, and then the nitrogen was cut off and water vapor was introduced, and then the temperature was kept at this temperature for 30 minutes. Then the furnace temperature was lowered to 1000°C at a cooling rate of 3°C / min, and then the temperature was kept at this temperature for 70 minutes.

[0137] (3) Turn off the water vapor and introduce nitrogen, and naturally cool to room temperature under the protection of nitrogen to obtain ultra-high structure and high specific surface carbon black based on high crystallinity.

[0138] Example 4

[0139] This embodiment provides a method for preparing a battery, comprising the following steps:

[0140] (1) Weighing positive electrode active materials lithium iron phosphate, polyvinylidene fluoride and carbon black in a mass ratio of 96:2:2, and mixing them evenly in an appropriate amount of N-methylpyrrolidone to obtain an electrode slurry;

[0141] (2) coating the electrode slurry obtained in step (1) onto a 16 μm thick aluminum foil (current collector), drying, rolling, and cutting to produce a positive electrode sheet;

[0142] (3) A button cell was prepared using a lithium metal sheet as a counter electrode, a separator (model: Celgard 2500), and an electrolyte (1 mol / L lithium hexafluorophosphate dissolved in a volume ratio of 1:1:1 of dimethyl carbonate (DMC) / ethylene carbonate (EC) / ethyl methyl carbonate (EMC).

[0143] The carbon black used in the electrode slurry of each battery is the carbon black obtained in Examples 1 to 3, and the corresponding batteries are numbered as Example 4-1, Example 4-2, and Example 4-3, respectively.

[0144] Comparative Example 1

[0145] Comparative Example 1 provides a method for preparing a carbon black product, comprising the following steps:

[0146] (1) The raw carbon black is added into a 35 wt% nitric acid aqueous solution, treated at 150° C. for 2 h, and then washed with water and dried to obtain a pretreated raw carbon black.

[0147] (2) The raw carbon black sample pretreated in step (1) was placed in a rotary furnace, nitrogen was introduced for protection, and then the furnace temperature was raised to 1500°C at a heating rate of 5°C / min, and then the nitrogen was cut off and water vapor was introduced, and then the temperature was kept at this temperature for 30 minutes. Then the furnace temperature was lowered to 1050°C at a cooling rate of 3°C / min, and then the temperature was kept at this temperature for 70 minutes.

[0148] (3) Turn off the water vapor and introduce nitrogen, and naturally cool to room temperature under the protection of nitrogen to obtain a carbon black product.

[0149] Comparative Example 1 also provides a battery, which is prepared by referring to the method of Example 4, except that the carbon black therein is replaced with an equal weight of the carbon black of Comparative Example 1, and the obtained battery is numbered Comparative Example 1-1.

[0150] Comparative Example 2

[0151] Comparative Example 2 provides a commercially available carbon black.

[0152] Comparative Example 2 also provides a battery, which is prepared by referring to the method of Example 4, except that the carbon black therein is replaced with an equal weight of the carbon black of Comparative Example 2, and the obtained battery is numbered Comparative Example 2-1.

[0153] Experimental Example 1

[0154] Figure 1 This is a scanning electron microscope image of the carbon black obtained in Example 3 of the present invention, Figure 2The transmission electron microscope images of the carbon black prepared in Example 3 of the present invention at different magnifications. It can be seen from the figure that the ultra-high structure and high specific surface area carbon black based on high crystallinity prepared in the embodiment of the present invention maintains a microstructure similar to that of the raw carbon black, and has a grape-like porous chain branch structure, indicating that the oxidative etching of the present invention does not destroy the carbon black aggregate structure, so it has a better ability to absorb and retain liquid. At the same time, the oxidative etching of carbon black increases the mesoporous structure, and some of the primary particles of carbon black are etched and hollowed out, thereby improving the liquid absorption and retention capacity of the carbon black and increasing the path of ion conduction. In addition, it can be seen from the transmission electron microscope image that the carbon black prepared by the present invention has band-shaped or ring-shaped lattice stripes, which further illustrates that the carbon black prepared by the present invention has a higher degree of graphitization.

[0155] In addition, it can be seen from the transmission electron microscope that the primary particles of the carbon black prepared by the present invention are roughly spherical, and the primary particles of the carbon black do not collapse or dissociate due to oxidation etching. The average particle size of the primary particles of the carbon black of the present invention is 25 to 35 nm. Specifically, the average particle sizes of the primary particles of the carbon black of Examples 1 to 3 are shown in Table 1 respectively.

[0156] Table 1 Average particle size of primary particles of carbon black in different embodiments

[0157]

[0158]

[0159] Experimental Example 2

[0160] Raman spectroscopy test was performed on the carbon black prepared in different embodiments and comparative examples. The specific test method is: using a laser Raman spectroscopy device, several particles of the carbon black sample to be tested are placed on a glass slide, and scraped with a spatula for several times to make it flat, and the test is performed under the following test conditions: YAG laser (excitation wavelength): 514nm, number of lines: 600gr / mm, filter: D0.6, objective lens magnification: 100 times, exposure time: 150 seconds, cumulative number of times: 2 times.

[0161] Figure 3 to Figure 5 The Raman spectra of the carbon blacks prepared in Examples 1 to 3 of the present invention are respectively: Figure 6 is the Raman spectrum of the raw carbon black used in the embodiment of the present invention, Figure 7-Figure 8 They are the Raman spectra of the carbon black of Comparative Examples 1 and 2. As can be seen from the figure, the Raman spectrum of the carbon black prepared by the present invention has two characteristic peaks, namely the D Raman scattering peak and the G Raman scattering peak. The crystallite size La and crystallinity of the carbon black calculated according to the Raman spectrum are shown in Table 2.

[0162] Table 2 La and crystallinity of carbon black in different embodiments and comparative examples

[0163]

[0164] The crystallite size La can give an indication of the degree of graphitization, wherein a higher La value is associated with a higher degree of graphitization. From the above results, it can be seen that the carbon black prepared by the present invention has a higher degree of graphitization. The crystallite size La of the carbon black of Comparative Example 1 is The crystallite size is much lower than that of the raw carbon black, which is caused by the severe etching and dissociation of the crystallite of the raw carbon black in Comparative Example 1, which shows that although excessive etching can increase the specific surface area of ​​carbon black, the crystallinity decreases rapidly, affecting the performance of carbon black. The carbon black prepared by the present invention can obtain a high degree of graphitization, which is better than the commercially available carbon black in Comparative Example 2. When the carbon black prepared by the present invention is used as a conductive agent or carrier, the high degree of graphitization of carbon black can improve the conductive properties of the electrode active material and the compatibility with the electrolyte or improve the stability of the carrier material to ensure the activity of the catalyst.

[0165] The BET specific surface area and pore parameters of carbon black of different embodiments and comparative examples were further tested according to the method of GB / T 19587-2004. Specifically, the specific surface area and pore size distribution of carbon black were determined by nitrogen adsorption method, the sample was vacuum degassed at 250°C for 2h, and then the adsorption and desorption performance of the sample for N2 was measured in the range of p / p0 0 to 1 at liquid nitrogen (77k) temperature. The multi-point BET method was used to determine the specific surface area of ​​carbon black, the t-plot method was used to analyze the micropore area and micropore volume of the sample, and the DFT method (N2@77K in carbon slit pore QSDFT adsorption branch model) was used to calculate the pore size distribution of carbon black. The specific results are shown in Table 3.

[0166] Table 3 BET specific surface area and pore parameters of carbon black in different embodiments and comparative examples

[0167]

[0168] From the above data, it can be seen that the pore volume of the carbon black prepared by the present invention is as high as 1.2859 cm 3 / g, and the proportion of mesopore (2-50nm) pore volume is more than 84.6%. Compared with the raw carbon black and the carbon black of comparative example 2, the proportion of mesopore volume is increased, which improves the liquid retention capacity of carbon black and is beneficial to the loading of the catalyst.

[0169] According to the standard method of "GB / T 3780.2-2017 Carbon Black Part 2: Determination of Oil Absorption Value", the OAN of the carbon black of different embodiments and comparative examples is measured. The specific results are shown in Table 4.

[0170] Table 4 OAN of carbon black in different embodiments and comparative examples

[0171]

[0172]

[0173] Compared with the OAN of the raw carbon black, the carbon black prepared in Examples 1 to 3 of the present invention has increased, with the highest increase rate reaching 50.9%, so that the structure of the carbon black used as a conductive agent has sufficient length and liquid absorption and retention capacity, and can obtain good electrical conductivity and ion conductivity. In addition, due to excessive etching, the carbon black prepared in Comparative Example 1 has an unstable aggregate structure that is easy to break and some aggregates have been etched and destroyed into smaller aggregates, so its oil absorption value does not increase significantly with the intensification of etching.

[0174] Experimental Example 3

[0175] The aggregate size distribution curve of carbon black was measured using a disc centrifugal sedimentation particle size analyzer (Brookhaven Instruments Corporation, BI-DCP). The aggregate size distribution curves of the carbon black prepared in Examples 1 to 3 are shown in FIG. Figures 9 to 11 The aggregate size distribution curve of the raw material carbon black used in the embodiment is shown in Fig.12 The aggregate size distribution curve of carbon black of comparative examples 1 to 2 is shown in Figure 13-14 , and the aggregate size D50 value of carbon black was calculated based on the above results, see Table 5.

[0176] Table 5 Aggregate size D50 value of carbon black in different embodiments and comparative examples

[0177] serial number D50(nm) Example 1 84 Example 2 95 Example 3 68 Comparative Example 1 55 Comparative Example 2 85 Raw material carbon black 96

[0178] From the above test results, it can be seen that the aggregate size distribution curve of the carbon black prepared in Examples 1 to 3 does not change much relative to the aggregate size distribution curve of the raw carbon black, and is similar to the aggregate size distribution curve of the commercially available carbon black in Comparative Example 2. From the value of D50, it can be seen that the carbon black of the present invention after oxidation etching maintains the structural size of the aggregate of the raw carbon black, and does not substantially destroy the rich chain branch structure of the carbon black, which is consistent with the display results of the scanning electron microscope and the transmission electron microscope. The carbon black prepared in Comparative Example 1 is excessively etched, resulting in an unstable aggregate structure that is easy to break or the aggregate has been etched and destroyed into smaller aggregates, so the aggregate particle size is greatly reduced relative to the raw carbon black and the carbon black prepared in Examples 1 to 3, which will affect the liquid absorption and retention capacity of the carbon black.

[0179] Fig.15The XRD spectra of the carbon black of Examples 1 to 3 and Comparative Examples 1 to 2 of the present invention and the raw carbon black. It can be calculated from the XRD spectrum data that the average lattice spacing d(002) of the carbon black of Examples 1 to 3 is 0.3534nm, 0.3510nm, and 0.3479nm, respectively, while the average lattice spacing d(002) of the raw carbon black is 0.3546nm. The average lattice spacing d(002) of the etched carbon black is smaller than that of the raw carbon black. Surface etching reduces the lattice spacing and improves the crystallinity of the carbon black. The average lattice spacing d(002) of the carbon black obtained in Examples 1 to 3 is close to or less than 3.500nm. It can be said that the carbon black obtained in Examples 1 to 3 is graphite carbon, which improves the stability of the carbon black. In addition, the average lattice spacing d(002) of the commercially available carbon black in Comparative Example 2 is 0.3591 nm, and the average lattice spacing d(002) of Examples 1 to 3 of the present invention is greatly reduced compared with Comparative Example 2, indicating that the degree of graphitization of the carbon black prepared in Examples 1 to 3 is higher than that of the commercially available carbon black. In addition, the average lattice spacing d(002) of the carbon black prepared in Comparative Example 1 is 0.3725 nm, which is much higher than the d(002) of graphite carbon, indicating that excessive etching reduces the degree of graphitization of carbon black.

[0180] Further based on Fig.15 The XRD data show that the crystallite sizes Lc of the carbon blacks prepared in Examples 1 to 3 of the present invention are The crystallite size Lc of raw carbon black is The crystallite size Lc of the commercially available carbon black in Comparative Example 2 is It can be seen that the crystallite size Lc of the carbon black prepared in the embodiment of the present invention is increased by up to 38.5% relative to that of the raw carbon black, which greatly improves the crystallinity of the carbon black, which is consistent with the analysis of the average lattice spacing d(002). At the same time, the crystallite size Lc of the carbon black prepared in the embodiment of the present invention is also greatly increased relative to that of the commercially available carbon black, indicating that the degree of graphitization of the carbon black prepared in the present invention is higher than that of the commercially available carbon black. In addition, the crystallite size Lc of the carbon black prepared in Comparative Example 1 is The crystallite size Lc of the carbon black prepared in Example 1 is much lower than that of Examples 1 to 3 and Comparative Example 2. Analysis shows that this may be due to the severe etching and dissociation of the crystallites, which leads to a significant reduction in the crystallite size Lc of the carbon black prepared in Comparative Example 1, thereby reducing the crystallinity.

[0181] Experimental Example 4

[0182] The performance of the batteries prepared in Example 4 and Comparative Examples 1-2 was tested, and the testing method included:

[0183] (1) -20℃ low temperature discharge test method: The assembled button battery is placed at room temperature for 16 hours, and then charged and discharged at a low current of 0.1C for 3 times. The battery is then placed in a 25℃ constant temperature box for 1C charge and discharge, and then fully charged. The fully charged battery is placed in a -20℃ constant temperature box for 12 hours, and finally discharged at 1C. The ratio of the discharge capacity at -20℃ to the discharge capacity at 25℃ is the -20℃ low temperature discharge efficiency.

[0184] (2) High-temperature discharge test method at 55°C: The assembled button battery is placed at room temperature for 16 hours and charged and discharged at a low current of 0.1C three times. The battery is then placed in a 25°C constant temperature box for 1C charge and discharge, and then fully charged. The fully charged battery is placed in a 55°C constant temperature box for 5 hours and finally discharged at 1C. The ratio of the discharge capacity at 55°C to the discharge capacity at 25°C is the 55°C high-temperature discharge efficiency.

[0185] The specific test results are shown in Table 6.

[0186] Table 6 Battery performance test results of different embodiments and comparative examples

[0187] Product / Parameter -20℃ low temperature discharge efficiency 55℃ high temperature discharge efficiency Example 4-1 56.3% 102.5% Example 4-2 56.9% 102.1% Example 4-3 57.5% 101.5% Comparative Example 1-1 56.0% 100.6%

[0188] Under low temperature conditions, lithium ion energy is low and the transmission capacity is poor, and the transmission of ions must jump over the contact interface barrier of the particles. Under the same addition amount, the carbon black with high specific surface area is distributed and covers the surface of the active particles. The number of particles is larger, which can form a good conductive network, reduce the ion transmission path, and improve the conductivity of the active material at low temperatures. At the same time, the carbon black with high crystallinity reduces the surface resistivity and increases the migration rate of electrons, which is conducive to the discharge capacity at low temperatures, thereby improving the discharge efficiency at low temperatures. Although the comparative example 2 has a higher specific surface area, due to its low crystallinity and many defects, the amount of carbon black that truly plays a conductive role is lower than the amount of carbon black prepared in Example 3 of the present invention. Therefore, the low-temperature discharge efficiency of the battery of Example 4-3 is slightly better than that of the battery of Comparative Example 2-1.

[0189] Discharging at high temperature is conducive to the discharge capacity, but carbon black with high specific surface area has more side reactions at high temperature, especially carbon black with low crystallinity, which has more defects and aggravates the occurrence of side reactions. The carbon black in Example 3 and Comparative Example 2 has high specific surface area and low crystallinity, and the high-temperature discharge efficiency of the corresponding batteries is lower than the high-temperature discharge efficiency of the batteries corresponding to the carbon black in Examples 1 and 2. Since the crystallinity of the carbon black in Example 3 is higher than that of the carbon black in Comparative Example 2, the high-temperature discharge efficiency of the battery in Example 4-3 is slightly better than that of the battery in Comparative Example 2-1.

[0190] In addition, from the above-mentioned low-temperature and high-temperature performance test results, it can be seen that the carbon black prepared in Comparative Example 1, although having a higher specific surface area, has a lower degree of crystallinity, a low intrinsic conductivity and is prone to side reactions. The discharge efficiency of the prepared button battery at -20°C and 55°C is lower than the discharge efficiency of the battery corresponding to the carbon black in other embodiments.

[0191] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. Ultra-high structure, high specific surface carbon black based on high crystallinity, characterized in that: The carbon black meets the following characteristics: (1) Crystallinity ≥ 39%; (2) BET specific surface area is 200 to 763 m 2 / g; (3) OAN is 334-548 mL / 100 g; (4) The average particle size of primary particles is ≤35nm; The average lattice spacing d(002) of the carbon black is ≤0.3534nm; The carbon black is prepared from raw carbon black with a crystallinity of ≥44%.

2. The ultra-high structure and high specific surface carbon black based on high crystallinity according to claim 1, characterized in that: Satisfy at least one of the following characteristics: (1) The crystallite size Lc of the carbon black is 20.03 to 25.17 Å; (2) The average lattice spacing d(002) of the carbon black is 0.3479 to 0.3534 nm.

3. The ultra-high structure and high specific surface carbon black based on high crystallinity according to claim 1, characterized in that: The crystallite size La of the carbon black is 27.8 to 37.5 Å.

4. The ultra-high structure and high specific surface carbon black based on high crystallinity according to claim 1, characterized in that: The lattice stripes of the primary particles of the carbon black are in irregular bamboo-hat-shaped bands or rings.

5. The ultra-high structure and high specific surface carbon black based on high crystallinity according to claim 1, characterized in that: The crystallinity of the carbon black is 39% to 46%.

6. The ultra-high structure and high specific surface carbon black based on high crystallinity according to claim 1, characterized in that: Satisfy at least one of the following characteristics: (1) The aggregate size of the carbon black is D50≤95nm; (2) The aggregate size D50 of the carbon black is ≥68 nm; (3) The average particle size of the primary particles of the carbon black is 25 to 35 nm; The aggregate size of the carbon black is measured using a disc centrifugal sedimentation particle size analyzer.

7. The ultra-high structure and high specific surface carbon black based on high crystallinity according to claim 1, characterized in that: Satisfy at least one of the following characteristics: (1) The average pore size of the carbon black is 5.86 to 9.04 nm; (2) The volume of pores with a size of 2 to 50 nm measured by nitrogen desorption of the carbon black is 0.3157 to 1.2061 cm 3 / g; (3) In the carbon black, the volume of pores with a size of 2 to 50 nm accounts for 84.6% to 93.8% of the total pore volume.

8. The method for preparing ultra-high structure and high specific surface carbon black based on high crystallinity according to any one of claims 1 to 7, characterized in that: The steps include: The pretreated raw carbon black is subjected to activation etching treatment; The activation etching process comprises: heating to a first activation temperature under a protective atmosphere, performing an activation process under the action of an activation gas; then cooling to a second activation temperature, performing an etching process under the action of an activation gas; and then cooling to room temperature under a protective atmosphere; The pretreatment comprises: treating the raw carbon black in an aqueous solution containing an oxidant at 30 to 150° C. for 0.5 to 2 hours, washing and drying; The first activation temperature is 1100-1500° C.; the second activation temperature is 900-1000° C.; and the crystallinity of the raw carbon black is ≥44%.

9. The preparation method according to claim 8, characterized in that: The BET specific surface area of ​​the raw carbon black is 60 to 150 m 2 / g.

10. The preparation method according to claim 8, characterized in that: The raw material carbon black is acetylene black.

11. The preparation method according to claim 8, characterized in that: The activated gas includes at least one of nitrogen dioxide, nitric oxide, CO2, CO, oxygen, ozone and water vapor.

12. The preparation method according to claim 8, characterized in that: The activation treatment time at the first activation temperature is 10 to 30 minutes; The etching treatment time at the second activation temperature is 30 to 70 minutes.

13. The preparation method according to claim 8, characterized in that: During the cooling, the cooling rate is 2-4°C / min.

14. The preparation method according to claim 8, characterized in that: During the heating, the heating rate is 4-6°C / min.

15. The preparation method according to claim 8, characterized in that: The oxidant includes at least one of hydrogen peroxide and an oxygen-containing acid.

16. The preparation method according to claim 15, characterized in that: The oxygen-containing acid includes at least one of nitric acid, sulfuric acid, hypochlorous acid and perchloric acid.

17. An electrode slurry, characterized in that: It comprises the ultra-high structure and high specific surface carbon black based on high crystallinity as described in any one of claims 1 to 7 or the ultra-high structure and high specific surface carbon black based on high crystallinity obtained by the preparation method as described in any one of claims 8 to 16.

18. A secondary battery, characterized in that: It comprises a positive electrode, a negative electrode, an electrolyte and a separator; at least one of the positive electrode and the negative electrode is made of the electrode slurry according to claim 17.

19. A fuel cell, characterized in that: The invention comprises a catalyst, wherein the catalyst comprises a carrier and active catalyst particles supported on the carrier; the carrier comprises the ultra-high structure and high specific surface carbon black based on high crystallinity as described in any one of claims 1 to 7 or the ultra-high structure and high specific surface carbon black based on high crystallinity obtained by the preparation method as described in any one of claims 8 to 16.

Citation Information

Patent Citations

  • Method for preparing active carbon from scrap tire pyrolytic carbon black

    CN106241803A

  • Method for preparing nano-porous superconductive carbon black through high-temperature composite activation modification and application of nano-porous superconductive carbon black

    CN117004255A

  • Lithium ion cell, anode therefor and preparing method thereof

    CN1949561A